An evaluation of the genetic diversity of Xylella fastidiosa isolated from diseased citrus and coffee in São Paulo, Brazil - Qin, X. T.; Miranda, V. S.; Machado, M. A.; Lemos, EGM; Hartung, J. S. (Amer Phytopathological Soc, 2001)
Strains of Xylella fastidiosa, isolated from sweet orange trees (Citrus sinensis) and coffee trees (Coffea arabica) with symptoms of citrus variegated chlorosis and Requeima do Cafe, respectively, were indistinguish able based on repetitive extragenic palindromic polymerase chain reaction (PCR) and enterobacterial repetitive intergenic consensus PCR assays. These strains were also indistinguishable with a previously described PCR assay that distinguished the citrus strains from all other strains of Xylella fastidiosa. Because we were not able to document any genomic diversity in our collection of Xylella fastidiosa strains isolated from diseased citrus, the observed gradient of increasing disease severity from southern to northern regions of São Paulo State is unlikely due to the presence of significantly different strains of the pathogen in the different regions. When comparisons were made to reference strains of Xylella fastidiosa isolated from other hosts using these methods, four groups were consistently identified consistent with the hosts and regions from which the strains originated: citrus and coffee, grapevine and almond, mulberry, and elm, plum, and oak. Independent results from random amplified polymorphic DNA (RAPD) PCR assays were also consistent with these results; however, two of the primers tested in RAPD-PCR were able to distinguish the coffee and citrus strains. Sequence comparisons of a PCR product amplified from all strains of Xylella fastidiosa confirmed the presence of a CfoI polymorphism that can be used to distinguish the citrus strains from all others. The ability to distinguish Xylella fastidiosa strains from citrus and coffee with a PCR-based assay will be useful in epidemiological and etiological studies of this pathogen.